Pola Komunikasi Organisasi untuk Menciptakan Kondusivitas Kerja di Bali in Bali Souvenir : Organizational Communication Patterns for Creating Work Conduciveness in Bali in Bali Souvenir - Gusti Ayu Dinda Pringga Dewi; Anak Agung Mia Intentilia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Organizational communication is a crucial aspect to ensure the flow of workplace interactions and to minimize potential internal conflicts. This study aims to analyze the communication patterns applied in managing internal work dynamics at Bali in Bali Souvenir. This study applied a qualitative descriptive approach. Data gathered through observation, interviews, and documentation with seven purposively selected informants, consisting of a supervisor, an admin, senior employees, junior employees, and a supplier of Bali in Bali Souvenir. The findings indicate that the dominant communication patterns are downward and horizontal communication, which function in conveying instructions, coordinating task implementation, and addressing operational issues. Although these patterns are considered effective in ensuring message clarity and fostering a conducive work atmosphere, several obstacles remain, including delays in information delivery, message alterations, and limited direct communication from subordinates to superiors. These findings highlight the importance of integrating formal and informal communication to enhance organizational adaptability in dealing with complex work dynamics. Therefore, strengthening two-way communication and external communication more systematically are essential to improve organizational effectiveness in the future.